Organic waste management based on supply chain management using arena simulation and macro ergonomics approach - Setyaningrum, Ratih; Sari, Pitri Nopita (OPSI, 2023)
In this modern era, simulation software such as Arena has become a valuable tool for designing, optimizing, and analyzing the flow of supply chains efficiently. The aim of this research is to describe and analyze the flow of waste supply chains using Arena software. The second objective is to analyze the behavior of the people of Semarang city regarding organic waste processing using a macroergonomics approach. This study employs a simulation approach by utilizing Arena software to model the flow of waste supply chains from collection, sorting, processing, to final disposal stages. Using Arena software, simulation results can be measured and objectively analyzed, serving as a basis for identifying improvements and enhancements in the waste supply chain. To manage organic waste in an area it is necessary to involve cognitive, psychological, organizational and environmental aspects. The strategy for managing organic waste in urban areas such as the Semarang area is to manage and ensure that organic waste has added value and sales value.